2010
DOI: 10.1002/j.0022-0337.2010.74.12.tb05014.x
|View full text |Cite
|
Sign up to set email alerts
|

Minority Dental Faculty Development: Responsibility and Challenge

Abstract: Over at least the last twenty years, the American Dental Education Association (ADEA) has given attention and priority to increasing the number of underrepresented minority (URM) dental school applicants, enrollees, and faculty members and to meeting the challenges of achieving diversity in the oral health workforce of the future as racial and ethnic minorities continue to grow and are expected to comprise more than 50 percent of the U.S. population by the middle of the twenty-irst century. Dental schools have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…The initiative supports grant applicants who are members of underrepresented minority groups, disabled, or from socially, economically, or educationally disadvantaged backgrounds. Other articles describe similar programs aimed at increasing the number of individuals from underrepresented minority groups who pursue academic careers in dentistry (Sinkford, Valachovic, Weaver, & West, 2010) and medicine (Daley et al, 2011).…”
Section: Academic Career Development 14mentioning
confidence: 99%
“…The initiative supports grant applicants who are members of underrepresented minority groups, disabled, or from socially, economically, or educationally disadvantaged backgrounds. Other articles describe similar programs aimed at increasing the number of individuals from underrepresented minority groups who pursue academic careers in dentistry (Sinkford, Valachovic, Weaver, & West, 2010) and medicine (Daley et al, 2011).…”
Section: Academic Career Development 14mentioning
confidence: 99%
“…In response to the faculty shortage, Bertolami urged dental schools to expose students and residents to academic careers 25 . Programs are therefore needed to identify, support, and mentor dental students who indicate an interest in academia 26 . Previous studies found that teaching assistantships, fellowships, and peer tutoring opportunities were helpful for the recruitment and retention of faculty and thus should be elements of academic track programs 27 , 28 .…”
mentioning
confidence: 99%
“…Lack of access to mentoring and professional development is a particular challenge for URM faculty members 10 , 11 . The number of senior, experienced URM faculty members in U.S. dental schools who can serve as inspirations, role models, and career guides for junior colleagues is strikingly small.…”
Section: Dental Education Workforce Trendsmentioning
confidence: 99%
“…Ethnic minorities are expected to comprise more than 50 percent of the U.S. population by 2150. However, only 2,413 (12 percent) of the 20,052 dental students enrolled in U.S. dental schools in 2010 and less than 10 percent of dental faculty members were African American, Hispanic, or Native American 11 . In its 2003 report National Call to Action to Promote Oral Health , 12 the U.S. Department of Health and Human Services observed that “the patient pool of any health care provider tends to mirror the provider's own racial and ethnic background.…”
Section: Dental Education Workforce Trendsmentioning
confidence: 99%